In Situ Self‐Assembly of Ordered Organic/Inorganic Dual‐Layered Interphase for Achieving Long‐Life Dendrite‐Free Li Metal Anodes in LiFSI‐Based Electrolyte. (16th November 2020) - Wang, Jian; Yang, Jin; Xiao, Qingbo; Zhang, Jing; Li, Tie; Jia, Lujie; Wang, Zile; Cheng, Shuang; Li, Linge; Liu, Meinan; Liu, Haitao; Lin, Hongzhen; et al.
Abstract: Metallic lithium electrode with high capacity of 3860 mA h g −1 is the most promising candidate for rechargeable batteries. However, some inherent problems such as dendrite growth, uneven solid electrolyte interphase (SEI), and high manufacturing risk restraint its practical application. Herein, distinct from the conventional mosaic structure, a facile fabrication of in situ self‐assembled organic/inorganic hybrid SEI with ordered dual‐layer structure on the lithium surface to suppress dendrite formation is proposed. With the aid of moderate active fluoric‐containing ionic liquid, the as‐formed lithium fluoride and robust ordered organic moieties are in situ self‐assembled on the metallic lithium surface. The evolution process of the dual‐layered structure is revealed by X‐ray spectroscopy, in situ sum frequency generation spectroscopy, and atomic force microscopy. The formed "double protection" ordered hybrid interphase layer also exhibits the surprising ability against the corrosion of carbonate electrolyte or dry air. As a consequence, the pretreated metallic lithium electrode represents excellent stripping/plating reversibility of ≈99% and a long lifespan up to 1200 h without formation of dendrite, and remains high performance at a current density of 10 mA cm −2, which is much higher than most reports, showing the facilitating promising to the future utilization. Abstract : A self‐assembled organic/inorganic hybrid solid electrolyte interphase (SEI) with an ordered bilayer structure is designed on the metallic lithium surface to suppress dendrite formation, as revealed by X‐ray spectroscopy, in situ sum frequency generation spectroscopy, and atomic force microscopy. Consequently, the pretreated metallic lithium electrode represents excellent stability and long lifespan, showing promise for future utilization.